Simulation of Active Sallen Key Notch Filter Circuit Using Circuit Wizard and Its Real Testing - Syifaul Fuada; Cindy Liu; Sri Anggraeni; Maulida Yasmin; Futuh Balad; Verra Halizzah; Devi Anassafila; Tryadi Herlambang Wijaya; Widias Tuti; Yee Mei Heong (Universitas Medan Area, 2023)
An electronic circuit that functions to block or hold signals with intermediate frequencies (median) and will forward signals between low frequencies and high frequencies is the definition of a Notch Filter. The Band Stop Filter, also often referred to as the Notch Filter, is a combination of a Low Pass Filter and a High Pass Filter connected in parallel. This connection differs from the Band Pass Filter, which connects the Low Pass Filter and High Pass Filter in series. This study aims to discuss the simulation of the Sallen-key notch filter Circuit. The author also conducts real simulations to prove the Circuit by changing or adjusting the value of the components installed in the Circuit so that the frequency response is according to the target. The purpose and role of the Sallen-key notch filter and the working principle of the theory of each filter used. The research method used in the research work is to carry out virtual simulations using virtual simulators and live simulations